Análisis lingüístico-comunicativo del tratamiento informativo de la guerra de Irak en la prensa venezolana - Sylvia Fernández Franco (Amnis)
In this paper, the informative treatment for the conflict originated by the publication of Mahoma’s cartoons is analyzed using two newspaper texts as sample: an opinion article from El País (Spain) and an informative piece from Panorama (Venezuela). Based on the linguistic- communicative model from Molero (1985-2003), Cabeza (1989-2006) and Franco (2000-2004), the analysis starts from the discourse level up to the conceptualization to contrast both journalistic genres and their author’s discursive strategies in the construction of the communicative situation. Subsequently, the processes developed to represent the conflict linguistically are revised, from the referential to the discursive level, in order to introduce production models that can contribute to mediation through a conscious and rational use of language. It was concluded that the journalistic language analyzed contributed to the polarization of readers instead of facilitating their consensus, which is why we encourage further research aimed to delineate textual production models that are suitable for managing conflicts.